2022
DOI: 10.1039/d2cp00607c
|View full text |Cite|
|
Sign up to set email alerts
|

Successive protonation of Lindqvist hexaniobate, [Nb6O19]8−: electronic properties and structural distortions

Abstract: Lindqvist Hexaniobate, [Nb6O19]8-, is an intriguing type of polyoxoniobate presenting a significant negative charge, high symmetry, robust structure and applications in photocatalysis. In this work, the [Nb6O19]8- polyanion was submitted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…In theoretical studies, Steffler et al. reported triply protonated states similar to that in our [H 3 (Nb 6 O 19 )] 5− model [25] . Thus, for n =4–7, we referred to their reported models and optimized the structure with solvation; for quadruply protonated [H 4 (Nb 6 O 19 )] 6− , the protonation to O t was more favorable than that to O b , and further proton adsorption ( n =5–7) occurred at O b [25] .…”
Section: Resultssupporting
confidence: 86%
“…In theoretical studies, Steffler et al. reported triply protonated states similar to that in our [H 3 (Nb 6 O 19 )] 5− model [25] . Thus, for n =4–7, we referred to their reported models and optimized the structure with solvation; for quadruply protonated [H 4 (Nb 6 O 19 )] 6− , the protonation to O t was more favorable than that to O b , and further proton adsorption ( n =5–7) occurred at O b [25] .…”
Section: Resultssupporting
confidence: 86%
“…[25] Thus, for n = 4-7, we referred to their reported models and optimized the structure with solvation; for quadruply protonated [H 4 (Nb 6 O 19 )] 6À , the protonation to O t was more favorable than that to O b , and further proton adsorption (n = 5-7) occurred at O b . [25] Based on the optimized structure, the O b sites of [H n (Nb 6 O 19 )] (8À n)À maintained relatively high NBO charges, while that of O t decreased with increasing protons. The NBO charges as a function of adsorbed proton numbers indicated that O b and O t of [H n (Nb 6 O 19 )] (8À n)À maintained its base property in the presence of additional protons.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…UV/Vis spectrometric titration revealed the degree of protonation of [Nb 6 O 19 ] 8À as a function of consumed base ] À were assigned with reference to Steffler et al [25]…”
Section: Forschungsartikelmentioning
confidence: 99%
See 2 more Smart Citations